Exploring temporal patterns of bacterial and fungal DNA accumulation on a ventilation system filter for a Singapore university library - Luhung, Irvan (2018)
Introduction: Ventilation system filters process recirculated indoor air along with outdoor air. This function inspires the idea of using the filter as an indoor bioaerosol sampler. While promising, there remains a need to investigate several factors that could limit the accuracy of such a sampling approach. Among the important factors are the dynamics of microbial assemblages on filter surfaces over time and the differential influence of outdoor versus recirculated indoor air. Methods: This study collected ventilation system filter samples from an air handling unit on a regular schedule over a 21-week period and analyzed the accumulation patterns of biological particles on the filter both quantitatively (using fluorometry and qPCR) and in terms of microbial diversity (using 16S rDNA and ITS sequencing). Results: The quantitative result showed that total and bacterial DNA accumulated monotonically, rising to 41 ng/cm2 for total DNA and to 2.8 ng/cm2 for bacterial DNA over the 21-week period. The accumulation rate of bacterial DNA correlated with indoor occupancy level. Fungal DNA first rose to 4.0 ng/cm2 before showing a dip to 1.4 ng/cm2 between weeks 6 and 10. The dip indicated a possible artifact of this sampling approach for quantitative analysis as DNA may not be conserved on the filter over the months-long service period. The sequencing results indicate major contributions from outdoor air for fungi and from recirculated indoor air for bacteria. Despite the quantitative changes, the community structure of the microbial assemblages was stable throughout the 21-week sampling period, highlighting the robustness of this sampling method for microbial profiling. Conclusion: This study supports the use of ventilation system filters as indoor bioaerosol samplers, but with caveats: 1) an outdoor reference is required to properly understand the contribution of outdoor bioaerosols; and 2) there is a need to better understand the persistence and durability of the targeted organisms on ventilation system filters.